Racial Discrimination, John Henryism, and Depression Among African Americans. (June 2016) - Hudson, Darrell L.; Neighbors, Harold W.; Geronimus, Arline T.; Jackson, James S.
Evidence from previous studies indicates that racial discrimination is significantly associated with depression and that African Americans with higher levels of socioeconomic status (SES) report greater exposure to racial discrimination compared to those with lower SES levels. Coping strategies could alter the relationship between racial discrimination and depression among African Americans. This study first examined whether greater levels of SES were associated with increased reports of racial discrimination and ratings of John Henryism, a measure of high-effort coping, among African Americans. Second, we examined whether high-effort coping moderated the relationship between racial discrimination and depression. Data were drawn from the National Survey of American Life Reinterview ( n = 2, 137). Analyses indicated that greater levels of education were positively associated with racial discrimination ( p < .001) and increased levels of racial discrimination were positively related to depression ( p < .001), controlling for all sociodemographic factors. Greater levels of John Henryism were associated with increased odds of depression but there was no evidence to suggest that the relationship between discrimination and depression was altered by the effects of John Henryism.